2021
DOI: 10.1002/cam4.4363
|View full text |Cite
|
Sign up to set email alerts
|

Safety of thoracic radiotherapy after PD‐(L)1 inhibitor treatment in patients with lung cancer

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In clinical trials of ICIs after conventional TRT, the incidences of any grade pneumonia and grade ≥ 3 pneumonia were 13–33% and 1–9%, respectively, compared with 56–62% and 2% observed in the real world [ 11 ]. In a previous study from our group, we observed a significant increase in the incidence and severity of treatment-related pneumonia in patients who underwent TRT after ICIs (grade ≥ 2, 48.96%; grade ≥ 3, 19.79%), and fatal pneumonia occurred in 6.25% of patients [ 42 ]. As the primary end point of this study, we observed that the incidence of all grades, grade 2 or higher, and grade 3 or higher pneumonia in the TRT group was 35.1%, 24.6%, and 5.2%, respectively, which was higher than that in the non-TRT group; however, a majority of patients recovered from pneumonia or remained stable.…”
Section: Discussionmentioning
confidence: 93%
“…In clinical trials of ICIs after conventional TRT, the incidences of any grade pneumonia and grade ≥ 3 pneumonia were 13–33% and 1–9%, respectively, compared with 56–62% and 2% observed in the real world [ 11 ]. In a previous study from our group, we observed a significant increase in the incidence and severity of treatment-related pneumonia in patients who underwent TRT after ICIs (grade ≥ 2, 48.96%; grade ≥ 3, 19.79%), and fatal pneumonia occurred in 6.25% of patients [ 42 ]. As the primary end point of this study, we observed that the incidence of all grades, grade 2 or higher, and grade 3 or higher pneumonia in the TRT group was 35.1%, 24.6%, and 5.2%, respectively, which was higher than that in the non-TRT group; however, a majority of patients recovered from pneumonia or remained stable.…”
Section: Discussionmentioning
confidence: 93%
“…A recent retrospective study in patients who underwent TRT after ICI evaluated the incidence and severity of treatment-related pneumonitis. It showed that the incidence and severity of treatment-related pneumonitis was significantly higher in lung cancer patients who received TRT after ICI ( 13 ). As is known, acute “radiation pneumonitis” usually occurs within 4 to 12 weeks after thoracic irradiation.…”
Section: Discussionmentioning
confidence: 99%